Vibrational Analysis of Brucite Surfaces and the Development of an Improved Force Field for Molecular Simulation of Interfaces - Zeitler, T.; Greathouse, J.; Gale, Julian; Cygan, R. (American Chemical Society, 2014)
We introduce a nonbonded three-body harmonic potential energy term for Mg–O–H interactions for improved edge surface stability in molecular simulations. The new potential term is compatible with the Clayff force field and is applied here to brucite, a layered magnesium hydroxide mineral. Comparisons of normal mode frequencies from classical and density functional theory calculations are used to verify a suitable spring constant (k parameter) for the Mg–O–H bending motion. Vibrational analysis of hydroxyl librations at two brucite surfaces indicates that surface Mg–O–H modes are shifted to frequencies lower than the corresponding bulk modes. A comparison of DFT and classical normal modes validates this new potential term. The methodology for parameter development can be applied to other clay mineral components (e.g., Al, Si) to improve the modeling of edge surface stability, resulting in expanded applicability to clay mineral applications.